2015
DOI: 10.1016/j.gerinurse.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' favorite activities are resoundingly active: Findings from the NHATS study

Abstract: Activity is associated with health among older adults yet older adults’ favorite activities have rarely been investigated. We analyzed the community dwelling, cognitively-intact sample of NHATS, a nationally representative sample of adults ≥65, who had named their favorite activities (N = 5247). Logistic regression models estimated the odds of choosing a physical activity controlling for demographics, self-rated health, and disability. For all ages, four of the top five most common favorite activities were act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…A recent study by Szanton and colleagues found that walking/jogging was the most favored activity among older adults [37]. Hence, one potential strategy to improve physical activity and to reap the health benefits of physical exercise among older adults with and without SCD is to encourage walking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Szanton and colleagues found that walking/jogging was the most favored activity among older adults [37]. Hence, one potential strategy to improve physical activity and to reap the health benefits of physical exercise among older adults with and without SCD is to encourage walking.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have participation for adults who are inactive, findings of older adults’ preferences indicated similar findings as participation where walking/jogging was the most preferred activity, followed by outdoor maintenance (including lawn and garden) and sports. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, walking or jogging was rated the highest among older adults' favorite activities in a large nationally representative sample of older adults [14]. …”
Section: Introductionmentioning
confidence: 99%